Analysis of Building Orientation and Window to Wall Ratio (WWR) Influence on Indoor Air Temperature Case Study FMIPA and FIAI Buildings, Universitas Islam Indonesia - Maulana, Mohamad Akbar; Sumarno, Muhammmad Rakhmatullah Ade; Handoko, Jarwa Prasetya Sih (Journal of Architectural Research and Design Studies, 2026)
Building orientation and the window-to-wall ratio (WWR) are two critical factors affecting thermal comfort in educational buildings located in tropical climates. This study aims to examine how orientation and variations in WWR influence indoor air temperature through case studies of the FMIPA and FIAI buildings at Universitas Islam Indonesia. Simulations were conducted using Computational Fluid Dynamics (CFD) to assess airflow and temperature distribution across different orientation and WWR scenarios. The results reveal that a north–south orientation yields a more stable temperature distribution, while a 40% WWR is optimal for balancing daylight and heat gain. The findings underscore the importance of passive design strategies in enhancing energy efficiency and thermal comfort in tropical educational facilities. Keywords: Building Orientation, Indoor Air Temperature, Thermal Comfort, Window-to-Wall Ratio (WWR), Educational Buildings